Differenes in Post-Injectable Contraceptive Fertility Recovery in the Independent Practice of Midwives - Ayu Nina Mirania; Stephanie Lexy Louis; Evi Yuniarti (GLOBAL HEALTH SCIENCE GROUP, 2026)
The Family Planning (KB) program is designed as a strategic effort to regulate birth intervals, number of children, and pregnancy for the creation of quality families. In the process of choosing a contraceptive method, the potential for side effects is one of the main considerations for couples to maintain birth distance. However, based on the data, the dominant factor that led to the discontinuation of the use of birth control in all types of methods was the desire to have offspring again, with a percentage reaching 34% The purpose of this study was to find out the difference in fertility recovery after injectable contraception. This type of research is descriptive comparatively with a cross sectional approach. The sample in this study was taken using a total sampling technique in accordance with the inclusion and exclusion criteria with a total of 62 respondents. Data collection techniques using factual data questionnaire instruments and analysis used using the Mann Whitney statistical test. The results of the study found that the average recovery time of injectable contraceptives was 1 month for 7.37 months while injectable 3 months for 13.3 months with a p value of 0.001<0.05 hai indicates a difference in fertility recovery from injectable contraceptives of 1 month and 3 months. The conclusion of this study is that there is a difference in fertility recovery after injectable contraception.